The Pemanfaatan Konten Digital dalam Upaya Peningkatan Promosi Pariwisata di Era 5.0 Society - Yaldi, Destri; Mareta, Yoan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
Technology developments are the main foundation in changing life in this digital era. The widespread use of technology is clear evidence that humans and technology cannot live separately. 5.0 society is the concept that technology will coexist with humans to improve a good quality of life. Tourism is one sector that can benefit from the 5.0 era of society. Through digital content, people can find tourist objects they want to visit by searching various digital media or what is often called social media. This research uses a conceptual review to review the use of digital content as an effort to increase tourism promotion in the era of 5.0 society.